Fishing for G‐Quadruplexes in Solution with a Perylene Diimide Derivative Labeled with Biotins. Issue 44 (10th July 2018) - Busto, Natalia; Calvo, Patricia; Santolaya, Javier; Leal, José M; Guédin, Aurore; Barone, Giampaolo; Torroba, Tomás; Mergny, Jean‐Louis; García, Begoña
Abstract: A new fluorescent, non‐cytotoxic perylene diimide derivative with two biotins at the peri position, PDI2B, has been synthesized. This molecule is able to interact selectively with G‐quadruplexes with scarce or no affinity towards single‐ or double‐stranded DNA. These features have made it possible to design a simple, effective, safe, cheap, and selective method for fishing G‐quadruplex structures in solution by use ofPDI2B and streptavidin coated magnetic beads. The new cyclic method reported leads to the recovery of more than 80 % of G‐quadruplex structures from solution, even in the presence of an excess of single‐stranded or duplex DNA as competitors. Moreover, PDI2B is a G4 ligand that can display higher thermal stabilization and greater affinity for 2‐ over 3‐tetrad quadruplexes, which constitutes a novel type of behavior. Abstract : Gone fishin′ : A new fluorescent, non‐cytotoxic perylene diimide derivative with two biotins at the peri position, PDI2B, has been synthesized. This molecule is able to interact selectively with G‐quadruplexes with scarce or no affinity towards single‐ or double‐stranded DNA. These features have made it possible to design a simple, effective, safe, cheap, and selective method to fish for G‐quadruplex structures in solution by use ofPDI2B and streptavidin‐coated magnetic beads.